Risks of all-cause mortality and major kidney events in patients with new-onset primary open-angle glaucoma: a nationwide long-term cohort study in Taiwan. Issue 3 (22nd March 2018) - Chou, Chu-Lin; Hsieh, Tsung-Cheng; Chen, Jin-Shuen; Fang, Te-Chao
Abstract : Objective: Cardiovascular risk factors are associated with primary open-angle glaucoma (POAG) in the general population. However, long-term mortality and major kidney events in patients with new-onset POAG remain unclear. Methods: Using the Taiwan National Health Insurance Research Database between 1997 and 2011, 15 185 patients with a new diagnosis of POAG were enrolled and propensity score matched (1:1) with 15 185 patients without ocular disorders (WODs). All-cause mortality and major kidney events were analysed by a multivariate Cox proportional hazards regression model and a competing risk regression model. Results: The risk of all-cause mortality was significantly higher in patients with new-onset POAG than in those WODs (adjusted HR (aHR) 2.11, 95% CI 1.76 to 2.54; p<0.001). Patients with POAG had higher risks of acute renal failure (ARF) (competing risk aHR 2.58, 95% CI 1.88 to 3.55; p<0.001) and end-stage renal disease (ESRD) (competing risk aHR 4.84, 95% CI 3.02 to 7.77; p<0.001) than those WODs. Conclusions: Our data demonstrate that POAG is a risk of all-cause mortality, ARF and ESRD, thus needing to notice mortality and major kidney events in patients with new-onset POAG.